2011
DOI: 10.1149/1.013111jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Microstructural Evaluation of Aged Nanostructured Thin Film Fuel Cell Electrocatalyst

Abstract: 3M's Nanostructured Thin Film (NSTF) electrode offers an alternative path to reduce Pt cost in a polymer electrolyte membrane fuel cell, owing to its unique extended surface structure. To understand the fuel cell performance and the durability of the electrode, it is necessary to know its microstructure. In this report, electrochemical and microstructural evaluations of the NSTF electrodes were done after different stages of ageing in a fuel cell. Changes over time of surface roughness, dealloying, and microst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 33 publications
(103 reference statements)
0
13
2
Order By: Relevance
“…Interestingly, a recent report has shown that the constituent units of extended thin films composed of polycrystalline 1D nanostructures were found to lose their unique 1D morphology in favor of forming a smooth flat film. 85 By contrast, the TEM results presented in Figure 8 and in our prior reports suggest that the unique 1D morphology of single-crystalline nanostructures presented herein is essentially preserved. Hence, the addition of 10% gold, forming a stabilized uniform alloy, resulted in substantial and quantifiable enhancements with respect to both ORR activity and durability.…”
Section: The Journal Of Physical Chemistry Letterscontrasting
confidence: 71%
See 1 more Smart Citation
“…Interestingly, a recent report has shown that the constituent units of extended thin films composed of polycrystalline 1D nanostructures were found to lose their unique 1D morphology in favor of forming a smooth flat film. 85 By contrast, the TEM results presented in Figure 8 and in our prior reports suggest that the unique 1D morphology of single-crystalline nanostructures presented herein is essentially preserved. Hence, the addition of 10% gold, forming a stabilized uniform alloy, resulted in substantial and quantifiable enhancements with respect to both ORR activity and durability.…”
Section: The Journal Of Physical Chemistry Letterscontrasting
confidence: 71%
“…Comparison of the durability results in the Pt–Pd 9 Au NWs with those obtained from state-of-the-art Pt NP/C catalysts substantiates our assertion that Pt–Pd 9 Au NWs possess superior durability performance. Interestingly, a recent report has shown that the constituent units of extended thin films composed of polycrystalline 1D nanostructures were found to lose their unique 1D morphology in favor of forming a smooth flat film . By contrast, the TEM results presented in Figure and in our prior reports suggest that the unique 1D morphology of single-crystalline nanostructures presented herein is essentially preserved.…”
contrasting
confidence: 39%
“…60 Non electronconducting supports have also been proposed, e.g. the Pt/NSTF from 3M, [64][65][66] but these materials failed to be implemented with success in PEMFC systems on the field, owing to the difficulty to deliver stable electrocatalytic performances in non-perfectly-controlled operation.…”
mentioning
confidence: 99%
“…[7][8][9][10] In addition, owing to its unique structure of an extended surface of Pt covering a support, one expects that the Pt or Pt-alloy layer thickness (and therefore the Pt loading) could be reduced while maintaining the electrochemical properties of the catalyst. 11 Therefore, NSTF catalyst technology provides a plausible pathway for achieving higher ORR activity using small amounts of Pt.…”
mentioning
confidence: 99%